Stress determination by in situ X-ray diffraction – Influence of water vapour on the Zircaloy-4 oxidation at high temperature. (15th April 2018) - Buscail, H.; Rolland, R.; Issartel, C.; Perrier, S.; Latu-Romain, L.
Highlights: Water vapour modifies the zirconia chemical state. Water vapour changes the oxide mechanical properties. Compressive stress is larger in dry air compared to the wet air at 500 °C. Water vapour leads to scale cracking during oxidation. In wet air, the lower growth stress is due to early stress relaxation. Abstract: A key parameter for the understanding the effect of water vapour on the oxidation mechanism is the determination of the stress level in the zirconia scale formed on Zircaloy-4 (Zy-4) at the operating temperature. In order to provide an accurate description of the structure and microstructure of the oxide layers, X-ray diffraction (XRD) analyses have been performed in situ under dry and wet oxidizing environments at high temperature on Zy-4 flat sheet samples. The aim of the present work is to show the influence of water vapour on the stress developed at high temperature in the oxide scale as well as inside the alloy. In situ growth stress determination in the oxide scale has shown that the compressive stress is larger in dry air compared to the wet air environment at 500 °C. In wet air, the lower growth stress is due to stress relaxation after the pre-transition stage. This is related to the effect of water vapour on the zirconia chemical state and change in the oxide mechanical properties leading to an earlier scale cracking.